Promoting reflection in asynchronous virtual learning spaces: Tertiary distance tutors’ conceptions - Bethany Alden Alden Rivers (Athabasca University Press, 2014)
Increasingly, universities are embedding reflective activities into the curriculum. With the growth in online tertiary education, how effectively is reflection being promoted or used in online learning spaces? Based on the notion that teachers’ beliefs will influence their approaches to teaching, this research sought to understand how a group of distance tutors at the UK Open University conceptualised reflection. It was hoped that these findings would illuminate their approaches to promoting reflection as part of their online pedagogies. Phenomenographic analysis indicated that these tutors conceptualised reflection in four qualitatively different ways. Furthermore, the data suggested that these educators held a combination of two conceptions: one that understood the origin of being reflective and one that understood the purpose of reflection. Analysis of structural aspects of these conceptions offered insight into tutors’ own perspectives for what is needed to make online learning environments fertile territory for reflective learning.